2013
DOI: 10.1111/exd.12216
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic signal molecules in skin biopsies of cutaneous lupus erythematosus: analysis using tissue microarray

Abstract: Cutaneous lupus erythematosus (CLE) is a heterogeneous autoimmune disease. Different pathogenetic mechanisms, including the accumulation of apoptotic keratinocytes in CLE, have been reported. Therefore, we investigated whether CLE and other inflammatory skin diseases differ with regard to the epidermal expression of molecules that are crucial for the initiation and regulation of apoptosis. In this study, 241 skin biopsies from patients with CLE, psoriasis (PSO), lichen planus (LP) and healthy controls (HCs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…18,19 Previous reports have found extensive apoptosis in nearly all the epidermis in CLE patients, with the exception of LE profundus 11 and higher apoptotic index (AI) in more acute forms of LE (subacute CLE (SCLE) and acute CLE (ACLE). 18 Toberer et al 21 found a significant increase in the TUNEL-and antiactivated caspase-3-positive keratinocytes in CLE and suggested an increased activity of the extrinsic apoptotic pathway in CLE.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Previous reports have found extensive apoptosis in nearly all the epidermis in CLE patients, with the exception of LE profundus 11 and higher apoptotic index (AI) in more acute forms of LE (subacute CLE (SCLE) and acute CLE (ACLE). 18 Toberer et al 21 found a significant increase in the TUNEL-and antiactivated caspase-3-positive keratinocytes in CLE and suggested an increased activity of the extrinsic apoptotic pathway in CLE.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the literature data on the TUNEL evaluations suggests that a higher number of apoptotic keratinocytes was demonstrated in LP compared with healthy controls, but lower when LP is compared with other inflammatory diseases (psoriasis and cutaneous lupus erythematosus) [74,75,76]. Our findings regarding psoriatic skin samples studied are in accordance with the aforementioned literature data suggesting that psoriasis is characterized by aberrant differentiation and arrest of natural apoptotic process; to some extent, TUNEL positivity can be associated with hyperproliferation, in which actively replicating DNA is more abundant or accessible to detection.…”
Section: Discussionmentioning
confidence: 99%
“…UV induces keratinocyte apoptosis, inflammatory cytokine production, and autoantigen exposure [23]. CLE lesions highly express Fas (CD95), which activates the extrinsic apoptotic pathway [24]. It is unclear whether UV drives enhanced apoptosis in lupus vs. control skin as two studies addressing this question have disparate findings[25, 26].…”
Section: Pathogenesismentioning
confidence: 99%